Gorlin-Goltz syndrome with familial manifestation - Pazdera, Jindrich; Santava, Alena; Kolar, Zdenek (Biomedical papers, 2022)
Aims. The detection of odontogenic keratocysts (OKC) in the oral cavity is one of the main criteria for the clinical manifestation of Gorlin-Goltz syndrome (Nevoid Basal Cell Carcinoma Syndrome - NBCCS). From a clinical point of view, we distinguish between ``syndromic'' and ``sporadic'' OKC. Syndromic cysts, often multifocal, may be an accidental finding on X-ray examination. They can manifest gradually depending on the development of permanent dentition. Sporadic cysts are rather solitary lesions with clinical manifestation in adulthood. Methods. Mutations in the PTCH1 gene are thought to be the cause of the clinical manifestation of NBCCS. These abnormalities can be transmitted from one generation to another and lead to a familial occurrence of the disease. In 35-50% of cases, these are a newly arising mutations. It is necessary to take into account the typical manifestations which in the next generation begin at a younger age and the disease usually has a more serious course. Results. We found a familial manifestation of NBCCS in two pairs of patients (mother and daughter and two siblings). Odontogenic keratocysts and cutaneous basal cell carcinomas were diagnosed and genetic testing revealed mutations in the PTCH 1 gene in all four individuals. Conclusions. With regard to the possibility of familial occurrence of NBCCS, it is necessary to pay increased attention to family history and, if necessary, to ensure clinical and genetic examination of parents and other family members. Patients of childbearing potential with evidence of NBCCS should be informed of the increased likelihood of the disease in the offspring.
Keywords: odontogenic keratocysts; Gorlin-Goltz syndrome (NBCCS); familial manifestations; genetic testing